Pengaruh Lokasi, Promosi Online dan Persepsi Harga Terhadap Keputusan Pembelian Konsumen - Ilham Ramdani Rahman; Depy Muhamad Pauzy; Titin Patimah (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the simultaneous and partial influence of location, online promotion and price perception on purchasing decisions at the Trening Reza Store Cikalang Tasikmalaya. The research method used in this research is quantitative research methods with a survey approach. The respondents in this research were 100 consumers of the Trening Reza Store Cikalang Tasikmalaya. The type of data used in this research is primary data obtained through a questionnaire. The data testing technique used in this research uses validity tests, reliability tests and classical assumption tests. Data analysis in this study used multiple regression analysis tools using SPSS version 25 software. The research results show that Location, Online Promotion and Price Perception simultaneously have a significant influence on Purchasing Decisions. Location partially has a significant effect on purchasing decisions. Online promotions partially have a significant effect on purchasing decisions. Price perception partially has a significant effect on purchasing decisions.